Clinical Characteristics of COVID-19 Patients with and without Diabetes in Wuhan Red Cross Hospital - Guozhen Li; Qin Deng; Jiali Feng; Fang Li; Nian Xiong; Qiong He (Journal of Diabetes Research)
Background. Since the end of December 2019, novel coronavirus- (SARS-CoV-2-) infected pneumonia (COVID-19) has spread rapidly in China. The study was designed to describe the clinical characteristics of COVID-19 patients with and without diabetes in Wuhan. Methods. 199 COVID-19 patients were admitted to Wuhan Red Cross Hospital in China from January 24th to March 15th. The cases were divided into the diabetic and nondiabetic groups according to the history of taking antidiabetic drugs or by plasma fasting blood glucose level at admission, and the differences between the groups were compared. A multivariable analysis of independent risk factors for in-hospital death was performed. Results. Among 199 COVID-19 patients, 76 were diabetic and 123 were nondiabetic. Compared with nondiabetics, patients with diabetes were older and had high levels of fasting plasma glucose (FPG), D-dimer, white blood cells, blood urea nitrogen (BUN), and total bilirubin (TBIL) and lower levels of lymphocytes, albumin and oxygen saturation (SaO2), and higher mortality (P<0.05). The two groups showed no difference in clinical symptoms. Diabetes (odds ratio (OR): 10.816, 95% CI (confidence interval): 1.895-61.741, P=0.007), higher level of D-dimer at admission (OR: 1.094, 95% CI: 1.017-1.178, P=0.016), and a lymphocyte count<0.6×109/L at admission (OR: 7.609, 95% CI: 1.087-32.049, P=0.006) were associated with increasing odds of death. Antidiabetic drugs were associated with decreasing odds of death. Treatment with low molecular weight heparin was not related to odds of death. Conclusion. The mortality rate of COVID-19 patients with diabetes was significantly higher than those without diabetes. Diabetes, higher level of D-dimer, and a lymphocyte count<0.6×109/L at admission were the risk factors associated with in-hospital death.